MECHANISMS FOR SALMONELLA INFECTION AND POTENTIAL MANAGEMENT OPTIONS IN CHICKEN - M. Mkangara; R. Mwakapuja; J. Chilongola; P. Ndakidemi; E. Mbega; M. Chacha (Journal of Animal and Plant Sciences, 2020)
Salmonella enterica is the largest species in genus Salmonella with its serovars responsible for infection in chickens and other warm-blooded hosts. After oral ingestion, Salmonella penetrates the mucosal layer of the gastrointestinal tract (GIT). It then provokes gastroenteritis and systemic infection to chickens of all ages depending on the serovar involved. The paper explains about Salmonella infection via Type Three Secretion System (TTSS) encoded Pathogenicity Islands (PIs) and how the bacterium survives the acidic environment of GIT.  It also explains the roles of TTSS-1 and TTSS-2 in translocation of effectors that interfere with host proteins and later internalisation of Salmonella in Salmonella-containing vacuole (SCV). Other virulence factors such as plasmid, biofilm and lipopolysaccharides are highlighted, and their importance in inducing pathogenicity to host was also included in the paper. Therefore, several factors are geared toward survival, infection, and replication of Salmonella in the host cells. Hence, this article explains the mechanisms of Salmonella infection in chicken, its persistence in different environments and the approaches in controlling chicken salmonellosis.
Keywords: Salmonella; Type three Secretion System; Pathogenicity Islands; Chicken; Infection